MENTAL HEALTH PROFILE OF PROSPECTIVE STUDENTS OF THE FACULTY OF HEALTH SCIENCES AT WONOSOBO AL QUR'AN SCIENCE UNIVERSITY IN 2024 - Sahli, Muhamad (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
Background: Students, typically aged 18-30, are individuals enrolled in higher education institutions and are granted special status due to their academic role. However, student life often involves heavy academic workloads, tight deadlines, and the constant pressure to perform well. These factors can take a toll on students' mental health, leading to stress, anxiety, and cognitive challenges. Objective: This study aimed to assess the mental health profile of prospective students at the Faculty of Health Sciences (FIKES), UNSIQ Wonosobo, in 2024. Methods: An analytic descriptive design was employed for this study, conducted at FIKES UNSIQ Wonosobo. The sample consisted of 160 prospective students from the regular class, selected using total sampling. Data was collected in September 2024 using a Self-Report Questionnaire that had been modified based on a literature review and validated for the study. Results: The study found that cognitive symptoms were most frequently reported by prospective students from the S1 Nursing program, with 24 respondents (70.5%) experiencing these symptoms. Many of these students had a vocational school (SMK) background (52.9%). Anxiety symptoms were also most prevalent among students from the S1 Nursing program, with 25 respondents (67.5%) affected. A majority of these students had a high school education background. These findings suggest a potential connection between educational background and the prevalence of mental health issues. This study underscores the mental health challenges faced by prospective students, emphasizing the need for support systems to help manage academic pressures and enhance student well-being.